A survey on the information needs of the Ramon Magsaysay (Cubao) High School students towards a proposed information literacy program for the library - Pavo, Dawn Daniel Christine M. (2009)
Possessing the skills to navigate through the vast information sources available today, or simply being information literate, is necessary to cope in the Information Age. School libraries play a vital role in honing the students to become information literate, thus, integration of information literacy programs offered by the school is deemed important.